Marine spatial planning and marine protected area planning are not the same and both are key for sustainability in a changing ocean - Catarina Frazão Santos; Lisa M. Wedding; Tundi Agardy; Julie M. Reimer; Elena Gissi; Helena Calado (npj Ocean Sustainability)
Abstract Marine spatial planning (MSP) and marine protected area (MPA) planning are two distinct area-based management processes that are often conflated. While engaging in MPA planning is crucially important for biodiversity conservation and localized sustainable use, it cannot bring the benefits that larger scale MSP can deliver. Confusing the two can lead not only to missed opportunities to support ocean sustainability, but also to inefficiencies and even conflict. Here, we clearly define and distinguish each approach, then discuss opportunities to optimise synergies, especially under rapidly changing climate. MSP can support conservation efforts by taking the broader context into account, while integrating conservation and MPA planning into MSP allows for the maintenance of ocean health—always a core goal of marine management.